Differentiation and characterization of osteoclasts from human induced pluripotent stem cells - Blümke, Alexander Felix; Simon, Jessica; Leber, Elizabeth; Scatena, Marta; Giachelli, Cecilia M. (Developmental biology, 2024)
Watch this Scientific Journal Video about Differentiation and Characterization of Osteoclasts from Human Induced Pluripotent Stem Cells at JoVE.com
Gesehen am 06.09.2024
Online veröffentlicht: 22. März 2024
Wissenschaftlicher Film. Deutschland. 2024
Keywords: Film